Raziskovanje čuječnosti pri študentih - Simčič, Blaž (Psihološka obzorja (Ljubljana), 2025)
In recent years, there has been a growing interest in the effects of mindfulness practice on students' mental health, well-being, and academic outcomes. To investigate these effects, it is necessary to provide valid and reliable measures of mindfulness, which are lacking in Slovenia. The purpose of this study was to examine the psychometric properties of the Slovenian version of the Philadelphia Mindfulness Scale (PHLMS) and its short form in a university student sample (N = 570) aged 18 to 39. The confirmatory factor analysis confirmed the proposed two-factor structure of the scale (both long and short versions), allowing the measurement of two independent mindfulness dimensions: Present-moment awareness and Acceptance. Internal consistency coefficients were satisfactory for both versions of the PHLMS scale. The scale also showed adequate convergent validity based on its positive correlation with the Mindful Attention and Awareness Scale (MAAS). Regarding gender differences in mindfulness, male university students scored higher in the acceptance subscale than female colleagues, while there were no significant gender differences in the present-moment awareness subscale. The Slovenian version of the PHLMS represents a valid and reliable measure of mindfulness in the context of higher education.
Keywords: čuječnost; Filadelfijska lestvica čuječnosti(PHLMS); gender differences; mindfulness; Philadelphia Mindfulness Scale; psihometrične značilnosti; psychometric properties; razlike med spoloma; študenti; university students